TENGKULAK DIGITAL: KONSEKUENSI KESENJANGAN DIGITAL PERDESAAN - Heryanto, Tonton; Luahambowo, Terserah; Atika, Novita; Pambudi, Angger; Sarfianto, Ari (Jurnal Insani, 2024)
The ijon trading system in rural communities in Indonesia has been entrenched for generations. It is plausible that the poverty experienced by farmers is a direct result of this ingrained system, which remains uneradicated despite numerous government initiatives aimed at improving farmers' welfare. The farmers' reliance on middlemen is deeply rooted, as these middlemen often serve as lifelines for farmers, especially in times of dire need. With the advent of digital technology (information and communication), social interactions have become faster and more efficient. However, in reality, the digital divide mirrors the social disparities present in everyday life. This study seeks to understand the digital divide between farmers and middlemen and to explore the underlying causes of this digital gap. The research adopts a qualitative approach, a form of social research that focuses on how individuals interpret and make sense of their experiences and the world they inhabit—in this case, the farmers and middlemen. The study concludes that the digital divide can indeed be seen as a reflection of the social divide in real life. The advancement of digital technology must be accompanied by government efforts to provide infrastructure for internet access and by enhancements in education. In doing so, the utilization of digital technology can ease the work of communities and contribute to equitable welfare.